A pilot randomised controlled trial of metacognitive therapy for prolonged grief. Issue 1 (9th January 2019) - Wenn, Jenine Anne; O'Connor, Moira; Kane, Robert T; Rees, Clare Samantha; Breen, Lauren J
Abstract : Objectives: Prolonged grief disorder is associated with significant distress and impairment and thus efforts to improve treatments are essential. The present pilot study tested the efficacy and feasibility of group Metacognitive Grief Therapy (MCGT) designed specifically for prolonged grief symptomatology to reduce the psychological distress and impaired function resulting from bereavement. Design/participants: Twenty-two bereaved adult participants with prolonged grief symptomatology were randomised to a wait-list control (n=10) or an intervention condition (n=12) with a 3-month and 6-month follow-up. The wait-list control group was offered treatment after the post-test assessment. Intervention: Participants attended six group MCGT sessions that ran for 2 hours per week. Outcome measures: A primary outcome measure of prolonged grief symptomatology and secondary outcome measures of depression, anxiety, rumination, metacognitive beliefs and quality of life were taken pretreatment and post-treatment for both groups and at the 3-month and 6-month follow-up for the intervention group. A Generalised Linear Mixed Model was used to assess treatment efficacy. Results: Post-treatment intent-to-treat analyses showed MCGT reduced prolonged grief symptomatology (Cohen's d=1.7), depression (d=1.3), anxiety (d=0.8), stress (d=1.0), rumination (d=0.9) and increased quality of life (d=0.6), and these effects were maintained at the 3-month and 6-month follow-ups. No prepost between-group differences were found in metacognitive beliefs. However, a large significant effect was identified at the 3-month and 6-month follow-ups (d=1.0). Conclusion: The results show promise for the utility of group MCGT for reducing psychological distress and promoting quality of life. Additionally, the results underscore the need for a full randomised controlled trial of group MCGT, which may be an important addition to the treatment armamentarium available to support people with prolonged grief. Trial registration number: ACTRN12613001270707; Results. Original protocol: BMJ Open 2015;5:e007221. doi:10.1136/bmjopen-2014-007221